ChemInform Abstract: Nanoscale Building Blocks in a Novel Lithium Arsenotungsten Bronze: Synthesis and Characterization. Issue 26 (June 2015) - Zhao, Pei; Mangir Murshed, M.; Huq, Ashfia; Grossmann, Henrike K.; Maedler, Lutz; Alekseev, Evgeny V.; Gesing, Thorsten M.
Abstract Polycrystalline Li3AsW7O25 is obtained by solid‐state reaction of LiNO3, WO3, and As2O5 in the molar ratio of 6:14:1, resp.